The spread of salmon lice (Lepeophtheirus salmonis Krøyer) from Norwegian fish farms and their impact on sea trout (Salmo trutta L.) - Serra-Llinares, Rosa Maria (Aquaculture Environment Interactions, 2020)
The transmission of salmon lice ( Lepeophtheirus salmonis Krøyer) from farm salmon to wild salmonids and the impact on wild populations are sources of intense debate in all salmon producing countries, and it is currently an issue of high political and economic relevance in Norway. Solid science-based evidence is therefore needed by decision makers to apply sound management strategies. Given the complexity of the systems, coupled with methodological challenges, the causal relation between the in-farm production of lice and increased lice abundances on wild salmonids have been difficult to demonstrate. In this thesis, mean salmon lice abundances on sea trout ( Salmo trutta L.) were shown to be directly correlated with the estimated number of lice emanating from nearby fish farms. Although temperature was found to also have an impact on lice epidemiology on both farmed and wild fish, temperature alone could not explain the high numbers of lice parasitizing sea trout in areas were farmed and wild fish coexist in close vicinity. This corroborates the hypothesis that salmon farms act as a main source of lice for sea trout in aquaculture-intensive areas in Norway, even after the effect of temperature has been accounted for. These conclusions were drawn based on the statistical analysis of a large and comprehensive data set combining information on standing stock and mean lice abundances on farmed fish from Norwegian salmon farms, together with observations of lice infestations on wild sea trout collected all along the Norwegian coast between 2010 and 2011. In combination, these two large and comprehensive data sets provided a unique opportunity to investigate the role of salmon farms as a source of lice for local sea trout populations. Moreover, results from this thesis suggest that the Norwegian National Salmon Fjords, i.e. protected areas subjected to strict limitations on aquaculture activities, can effectively protect wild salmonids against infestations with lice of farm origin, but only if the size and configuration of the protected area is adequate. Lice abundances on sea trout caught inside large National Salmon Fjords were found to be consistently low over time and are assumed to represent natural levels. Lice infestations on sea trout caught inside smaller National Salmon Fjords, on the contrary, showed large variation between years, oscillating in accordance with the variations in stocked biomass in the surrounding farms. Lice prevalence and intensities in these areas occasionally matched and even exceed those previously reported in areas of intensive farming in Norway. These results suggest that the production and transport of planktonic lice larvae from farms situated outside the limits of the protected areas might still be an important source of lice for local populations of sea trout. Although individual studies for each National Salmon Fjord may be necessary to evaluate the degree of protection, one can expect that the capacities of the smallest fjords for preventing the transmission of lice from farm salmon to wild fish are probably limited, and it is reasonable to assume that the protection of large areas contributes best to the protection of wild salmonids. The optimal design will in any case depend on the target species: while sea trout may benefit from the establishment of a local protected area covering their marine home range, the protection of Atlantic salmon may require the protection of entire fjords or the establishment of “clean corridors” along their migration routes. Last, this thesis delivers direct evidence of a causal relationship between salmon lice and marine mortality of sea trout in nature. Based on results from exposure field studies, combined with acoustic telemetry, this thesis shows a mortality hazard ratio of 2.7 (95% CI = 1.04−7.13) for lice-infested trout post-smolts compared to non-infested control individuals. In other words, the probability of a trout post-smolt to survive the first summer at sea was reduced by almost two-thirds when infested with a heavy lice load, although there is a big uncertainty around this estimate. These results apply to fish carrying a relative intensity of 2.4 lice g −1 , on average. Although such lice intensities are well beyond the estimated mortality-inducing threshold of 0.3 lice g −1 (Taranger et al. 2015), they are still representative of lice infestations observed on sea trout in some farm-intensive areas in Norway. Furthermore, this thesis documents an altered migration behavior of lice-infested individuals, including the abrupt interruption of the feeding migration after just a few weeks at sea and a preference for feeding areas closer to the river, in the inner part of the fjord. While control fish spent on average 100 days at sea before return, lice-infested sea trout returned to freshwater after only 18 days at sea, meaning that almost 80% of the feeding time at sea was lost because of salmon lice. This can be expected to significantly reduce marine growth and further have an impact at the population level. Studies that accurately quantify the impact of salmon lice on wild sea trout and their populations are still needed, and this thesis makes an important contribution in this direction.